The Falcon Test: An Observer Agreement Study in Subjects With and Without Anterior Knee Pain - Michael T. Cibulka; Payton Wunderlich; Hayden Klockenga; Andrew Reed; John Sandman (International Journal of Sports Physical Therapy)
# Introduction